2015
DOI: 10.3389/fmicb.2015.00359
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of α-glucosyl hesperidin of citrus fruits and epigallocatechin gallate of green tea on the Loss of Rotavirus Infectivity in Cell Culture

Abstract: A number of secondary plant metabolites (e.g., flavonoids) possess antiviral/antimicrobial activity. Most flavonoids, however, are difficult to study, as they are immiscible in water-based systems. The relatively new semisynthetic α-glucosyl hesperitin (GH), and the natural plant product epigallocatechin gallate (EGCG) are unique among most flavonoids, as these flavonoids are highly soluble. The antiviral activity of these plant metabolites were investigated using the rotavirus as a model enteric virus system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…A hesperidin derivate, alpha-glucosyl hesperidin, previously found in the orange peel by several authors [ 62 , 63 , 64 , 65 , 66 ] has been identified at time 8.481 min (peak 25). In addition, a naringin derivate found at peak 34 was assigned to naringin hydrate according with Iglesias-Carres et al [ 55 ] and Fayek et al [ 59 ].…”
Section: Resultsmentioning
confidence: 86%
“…A hesperidin derivate, alpha-glucosyl hesperidin, previously found in the orange peel by several authors [ 62 , 63 , 64 , 65 , 66 ] has been identified at time 8.481 min (peak 25). In addition, a naringin derivate found at peak 34 was assigned to naringin hydrate according with Iglesias-Carres et al [ 55 ] and Fayek et al [ 59 ].…”
Section: Resultsmentioning
confidence: 86%
“…In addition, hesperidin manages to regulate glucolipotoxicity and reduces neuropathic pain during DM. Similarly, on comparative analysis of hesperidin with other synthetic and/or naturally available antioxidants like butylated hydroxyanisole and hydroxytoluene (BHA and BHT), α-tocopherol and vitamin-C, it showed better scavenging effects on free radicals of H + and H 2 O 2 [19][20][21][22][23]. Moreover, synergistic efficacy of hesperidin with other citrus flavonoids for instance lemon flavonoids, like eriocitrin has also demonstrated admirable potential to reduce oxidative stress in diabetic rats [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Tests on laboratory animals have shown the ability of flavonoids to inhibit infection by various viruses such as herpes simplex-1, parainfluenza and respiratory syncytial virus [23,24], poliomyelitis-1 [25], rhinovirus [26,27], hepatitis C [28], rotavirus [29], influenza [30][31][32][33][34][35][36], SARS-coronavirus-1 [37]. Here we will examine recent evidence regarding the SARS-CoV-2 virus in more detail.…”
Section: Effects At Cellular Levelmentioning
confidence: 99%